2013
DOI: 10.1007/978-3-642-38004-4_2
|View full text |Cite
|
Sign up to set email alerts
|

Enforcing More with Less: Formalizing Target-Aware Run-Time Monitors

Abstract: Abstract. Run-time monitors ensure that untrusted software and system behavior adheres to a security policy. This paper defines an expressive formal framework, based on I/O automata, for modeling systems, policies, and run-time monitors in more detail than is typical. We explicitly model, for example, the environment, applications, and the interaction between them and monitors. The fidelity afforded by this framework allows us to explicitly formulate and study practical constraints on policy enforcement that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Our definition of policies extends that of security properties [22]: security properties are predicates, i.e., binary functions, on sets of traces, whereas we focus on policies that are functions whose range is the real numbers (as opposed to {0, 1}). We leave the investigation of enforcement for securities policies defined as sets of sets of traces (e.g., [22,8,19]) for future work.…”
Section: Cost Security Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our definition of policies extends that of security properties [22]: security properties are predicates, i.e., binary functions, on sets of traces, whereas we focus on policies that are functions whose range is the real numbers (as opposed to {0, 1}). We leave the investigation of enforcement for securities policies defined as sets of sets of traces (e.g., [22,8,19]) for future work.…”
Section: Cost Security Policiesmentioning
confidence: 99%
“…Drabik et al introduced a framework that calculated the overall cost of enforcement based on costs assigned to the enforcement actions performed by the monitor [10]; this framework can be used to calculate and compare the cost of different monitors' implementations. This framework provides means to reason about cost-aware enforcement, but its enforcement model does not capture interactions between the target and its environment, including the monitor; recent work has shown that capturing such interactions can be valuable [19]. In addition, in practice the cost of running an application may depend on the ordering of its actions, which may in turn depend on the scheduling strategy.…”
Section: Introductionmentioning
confidence: 99%
“…2 An important aspect of this formalism is the ability of the controller to prevent bad actions before they happen, meaning that the target is not directly aware that its action has been suppressed, and keeps going normally. More complex systems exist to represent the interaction between the target and the controller, such as [17,19]. Such an extension is considered as future work.…”
Section: Quantitative Control Operatorsmentioning
confidence: 99%
“…Our definition of policies extends that of security properties [22]: security properties are predicates, i.e., binary functions, on sets of traces, whereas we focus on policies that are functions whose range is the real numbers (as opposed to {0, 1}). We leave the investigation of enforcement for securities policies defined as sets of sets of traces (e.g., [22,8,19]) for future work.…”
Section: Cost Security Policy Enforcementmentioning
confidence: 99%
“…This includes Martinelli and Matteucci's model of run-time monitors based on CCS [21], Gay et al's service automata based on CSP for enforcing security requirements in distributed systems [13], Basin et al's language, based on CSP and Object-Z (OZ), for specifying security automata [1], and Mallios et al's I/O automata-based model for reasoning about incomplete mediation and knowledge the monitor might have about the target [19]. Although these models are richer and orthogonal revisions to security automata and related computational and operational extensions, they maintain the same view of (enforceable) security policies: binary predicates over sets of executions.…”
Section: Related Workmentioning
confidence: 99%